2022
DOI: 10.1029/2021ja030008
|View full text |Cite
|
Sign up to set email alerts
|

Flux Enhancements of Field‐Aligned Low‐Energy O+ Ion (FALEO) in the Inner Magnetosphere: A Possible Source of Warm Plasma Cloak and Oxygen Torus

Abstract: Flux enhancements of field‐aligned low‐energy O+ ion (FALEO) are simultaneously observed by Arase, Van Allen Probes A and B in the nightside inner magnetosphere during 05–07 UT on September 22, 2018. FALEOs appear after a magnetic dipolarization signature with approximately 6–20 min delay. It has the energy‐dispersion signature from a few keV to ∼100 eV only in the direction parallel to the magnetic field at Arase, while it decreases its energy from a few keV down to 10 eV in both the parallel and antiparallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Thus, the electric field drift would not affect the shape of arrival‐time curves much to first‐order approximation, as long as the MLT and L‐shell extent of IOOs is not too small (justified in Section 4.3). However, we suggest more detailed studies on IOOs should consider the effects of electric drift, especially those directly focusing on ion motions [see, e.g., Nosé et al., 2022].…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the electric field drift would not affect the shape of arrival‐time curves much to first‐order approximation, as long as the MLT and L‐shell extent of IOOs is not too small (justified in Section 4.3). However, we suggest more detailed studies on IOOs should consider the effects of electric drift, especially those directly focusing on ion motions [see, e.g., Nosé et al., 2022].…”
Section: Statisticsmentioning
confidence: 99%
“…Such fluctuations could cause further acceleration and pitch-angle scattering of IOOs. Recently, Nosé et al (2022) investigated in detail how IOOs evolve after they are extracted from the ionosphere at substorm onset. By tracing particle motion in a model magnetosphere (both magnetic and electric field are considered), the authors showed that, after several hours of their launch, O + ions would have a spatial distribution similar to those of the warm plasma cloak and oxygen torus, indicating inner-magnetosphere IOOs could be a source of the latter two.…”
mentioning
confidence: 99%
“…In addition, bounce echoes of ionospheric outflows have been observed in the inner magnetosphere (e.g., Gkioulidou et al., 2019; Nosé et al., 2022). These echoes, along with corresponding primary beams, have facilitated the identification of a novel outflow oxygen ion population in a statistical manner (Z.‐Y.…”
Section: Introductionmentioning
confidence: 99%